µ‐opioid receptor, β‐endorphin, and cannabinoid receptor‐2 are increased in the colonic mucosa of irritable bowel syndrome patients - Dothel, Giovanni; Chang, Lin; Shih, Wendy; Barbaro, Maria Raffaella; Cremon, Cesare; Stanghellini, Vincenzo; De Ponti, Fabrizio; Mayer, Emeran A.; Barbara, Giovanni; Sternini, Catia (Neurogastroenterology and motility, 2019)
Background and Aims The gut immune, cannabinoid, and opioid systems constitute an integrated network contributing to visceral sensation and pain modulation. We aimed to assess the expression of the µ‐opioid receptor (MOR), its ligand β‐endorphin (β‐END), and cannabinoid receptor‐2 (CB2) in patients with irritable bowel syndrome (IBS) and asymptomatic controls (AC) and their correlation with sex and symptom perception. Methods Mucosal biopsies were obtained from the left colon of 31 IBS patients (45% women) with predominant constipation (IBS‐C, 9) or diarrhea (IBS‐D, 10) or with mixed bowel habits (IBS‐M, 12) and 32 AC (44% women) and processed for qRT‐PCR, Western blotting, and immunohistochemistry. Key Results µ‐opioid receptor and CB2 mRNA and protein expression and β‐END protein levels were increased in patients with IBS compared to AC (all Ps=0.021). A significant sex by IBS interaction was found in relation to CB2 mRNA expression (P = .003) with women showing a markedly higher expression to men (P = .035). In contrast, in AC, men had higher expression than women (P = .033). β‐END, MOR, and CB2 immunoreactivities (IR) were localized to CD4+T cells including EMR‐1+ eosinophils and CD31+ T cells but not to mast cells. Conclusions The increased expression of MOR, β‐END, and CB2 in the mucosa of IBS patients, where they are localized to immune cells, suggests that opioid and cannabinoid systems play an immune‐related compensatory role in visceral pain in IBS patients. Further work is necessary to support this hypothesis. The purpose of this study was to determine whether Mu opioid receptor (MOR), its ligand β‐endorphin (β‐END) and the cannabinoid receptor‐2 (CB2) were altered in the colonic mucosa of patients with irritable bowel syndrome (IBS) vs asymptomatic controls (AC) using qRT PCR, Western Blot and immunohistochemistry with confocal microscopy. We found that MOR, β‐END, and CB2 (shown here in A & C) expression was increased in IBS vs AC subjects with a significant sex x IBS interaction with CB2 mRNA with higher CB2 mRNA in IBS women vs men but the opposite in AC (shown in B), and that MOR, β‐END, and CB2 immunoreactivity was localized to immune cells. These findings suggest an involvement of the opioid and cannabinoid systems in the immune response that might affect visceral sensation in IBS either through neuronal or alternative pathways.